2007
DOI: 10.1523/jneurosci.2381-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Golli Myelin Basic Proteins Enhances Calcium Influx into Oligodendroglial Cells

Abstract: , a specific blocker of voltage-operated Ca 2ϩ channels, abolished the ability of golli to promote process extension in a dose-dependent manner. Analysis of the golli protein identified a myristoylation site at the C terminus of the golli domain, which was essential for the action of golli on Ca 2ϩ influx, suggesting that binding of golli to the plasma membrane is important for modulating Ca 2ϩ homeostasis. High-resolution spatiotemporal analysis along N19 processes revealed higher-amplitude local Ca 2ϩ influx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 56 publications
5
97
0
Order By: Relevance
“…This cell line stains positive for both the NG2 and A2B5 antibodies, which are markers for oligodendroglial progenitor cells (OPCs), and also lacks expression of classic MBP and proteolipid protein mRNAs [45]. This cell line has previously been used to examine the effects of apotransferrin over-expression on OLG differentiation, elaboration of neurite cell processes in co-culture with neurons, and more recently, the effects of golli and classic MBP over-expression on calcium homeostasis and cell migration [7,38,[46][47][48]. Another interaction of classic MBP that has been studied in N19 cells is that with SH3-domaincontaining proteins such as Fyn, where we have demonstrated that disruption and/or pseudophosphorylation of the SH3-ligand in MBP has significant effects on cell morphology, and on the trafficking of the protein [35].…”
Section: Classic 185-and 215-kda Mbp Isoforms Localize To Membrane-mentioning
confidence: 99%
“…This cell line stains positive for both the NG2 and A2B5 antibodies, which are markers for oligodendroglial progenitor cells (OPCs), and also lacks expression of classic MBP and proteolipid protein mRNAs [45]. This cell line has previously been used to examine the effects of apotransferrin over-expression on OLG differentiation, elaboration of neurite cell processes in co-culture with neurons, and more recently, the effects of golli and classic MBP over-expression on calcium homeostasis and cell migration [7,38,[46][47][48]. Another interaction of classic MBP that has been studied in N19 cells is that with SH3-domaincontaining proteins such as Fyn, where we have demonstrated that disruption and/or pseudophosphorylation of the SH3-ligand in MBP has significant effects on cell morphology, and on the trafficking of the protein [35].…”
Section: Classic 185-and 215-kda Mbp Isoforms Localize To Membrane-mentioning
confidence: 99%
“…This cell line stains positive for both the NG2 and A2B5 antigens, which are markers for oligodendroglial progenitor cells (OPCs), and lacks expression of classic MBP and proteolipid protein mRNAs [35]. The N19-OLG line has been successfully employed in other studies, including specifically examining the effect of Golli and classic 18.5-kDa MBP over-expression on calcium homeostasis [13,20,40,41], and on the co-localization of 18.5-kDa MBP with cytoskeletal proteins and SH3-domain-containing proteins [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The conditionally-immortalized N19-OLG cell line (representing the O2A progenitor) was obtained from Dr. Anthony Campagnoni (UCLA Semel Institute for Neuroscience) 15,5 , and has been previously used to study molecular mechanisms of myelin gene expression and signal transduction leading to OLG differentiation (e.g. 6,10 ). We have found this cell line to be robust with respect to transfection with exogenous myelin basic protein (MBP) constructs fused to either RFP or GFP (red or green fluorescent protein) 13,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The dye, NucView 488 is released and enters the cell nucleus where it binds DNA and fluoresces green at 488 nm, signaling apoptosis. Use of the NucView 488 caspase-3 substrate allows for live-cell imaging in real-time 1,10 . In this video, we also describe the culturing and transfection of immortalized N19-OLG cells, as well as live-cell imaging techniques.…”
mentioning
confidence: 99%